Culture of Rodent Spermatogonial Stem Cells, Male Germline Stem Cells of the Postnatal Animal - Kubota, Hiroshi (2008)
Spermatogonial stem cells (SSCs), postnatal male germline stem cells, are the foundation of spermatogenesis, during which an enormous number of spermatozoa is produced daily by the testis throughout life of the male. SSCs are unique among stem cells in the adult body because they are the only cells that undergo self-renewal and transmit genes to subsequent generations. In addition, SSCs provide an excellent and powerful model to study stem cell biology because of the availability of a functional assay that unequivocally identifies the stem cell. Development of an in vitro culture system that allows an unlimited supply of SSCs is a crucial technique to manipulate genes of the SSC to generate valuable transgenic animals, to study the self-renewal mechanism, and to develop new therapeutic strategies for infertility. In this chapter, we describe a detailed protocol for the culture of mouse and rat SSCs. A key factor for successful development of the SSC culture system was identification of in vitro growth factor requirements for the stem cell using a defined serum-free medium. Because transplantation assays using immunodeficient mice demonstrated that extrinsic factors for self-renewal of SSCs appear to be conserved among many mammalian species, culture techniques for SSCs of other species, including farm animals and humans, are likely to be developed in the coming 5–10 years.